Corporate financing decisions when investors take the path of least resistance☆ - BAKER, M; COVAL, J; STEIN, J (Journal of Financial Economics, 2007)
We argue that inertial behavior on the part of investors can have significant consequences for corporate financial policy. One implication of investor inertia is that it improves the terms for the acquiring firm in a stock-for-stock merger, because acquirer shares are placed in the hands of investors, who, independent of their beliefs, do not resell these shares on the open market. In the presence of a downward-sloping demand curve, this leads to a reduction in price pressure and, hence, to cheaper equity financing. We develop a simple model to illustrate this idea and present supporting empirical evidence.